Interview with Prof Praveen Mishra - Shrestha, Rabindra Man; Acharya, Asal (Orthodontic Journal of Nepal, 2016)
Prof. Dr. Praveen Mishra was born in November 11, 1962 in Pipara, Mahottari district. He completed BDS from University of Bombay in 1985, MDS (Orthodontics) from Manipal Academy of Higher Education in 1995 and Post-doctoral Fellowship from MAHE (Mangalore) in 1996. Currently, he is the Professor and Head, Department of Orthodontics at Kantipur Dental College. He has served as Head, Department of Dental Surgery at NAMS (Bir Hospital); Chief of Oral Health Focal Point; Dean, National Academy of Medical Science; and Secretary, Ministry of Health & Population, Government of Nepal during 2009-14. He has also served as the President of Nepal Dental Association, Founder President of Orthodontics and Dentofacial Orthopedic Association of Nepal, Executive Member- Nepal Medical Council. He is the Visiting Professor at BP Koirala Institute of Health Sciences, Dharan; University Dental College, Dhaka. He is the Fellow of Academy of Dentistry International, International College of Dentists and Pierre-Fauchard Academy.